Encore: Behavioural animal models of stress, depression and mood disorders - Petković, Aleksa; Chaudhury, Dipesh (Frontiers in Behavioral Neuroscience, 2022)
Animal studies over the past two decades have led to extensive advances in our understanding of pathogenesis of depressive disorders. Among these, rodent behavioural models are believed to be of highest informative value. Here we present a comprehensive overview of the most popular behavioural models with respect to physiological, circuit and molecular biological correlates. Behavioural stress paradigms and behavioural tests are assessed in terms of outcomes, strengths, weaknesses, and translational value, especially in domain of pharmacological studies.